GOAL 4: Ensure inclusive and equitable quality education and promote lifelong opportunities for all - Government of Jamaica (My University, 2022)
The review for the period 2018-2022 summarizes key achievements, issues and challenges concerning quality education. The discussion notes the aim to ensure that all girls and boys complete free, equitable and quality primary and secondary education leading to relevant and effective learning outcomes by 2030.
Voluntary National review 2022
Keywords: Inclusive education, quality education